On coding standards for robotics and embedded systems - Pedro, Ana Marian M. (Animo Repository, 2011)
This paper investigates the importance of coding standards and the impact they have on robotic and embedded systems. Using the coding standards document from a Humanoid Robotics Course in Chalmers University of Technology as reference, improvements on format, documentation and provisions for safety critical code are discussed.